Relationship of Smartphone Usage and Academic Performance among Undergraduate students – A Systematic Review - Ancy Albert1 ; Nancy Netto1 ; Neelkant Pawar1 ; Fenilkumar Patel1 , Sharadha Ramesh2 ; Manisha Mistr (Indian Journal of Forensic Medicine & Toxicology, 2020)
Background: Smartphones have become the new normal of 21st century. With growing need to becomedigitally competent each individual is trying to own one smartphone or a similar gadget.Methodology: PRISMA guidelines were used to conduct a systematic review of Literature. 98 researcharticles were reviewed by the team using specific key words. They were scrutinized for their eligibility toget selected for further in-depth review. Articles were selected based on the appropriateness of the titles,abstracts, and results. After a thorough check only 06 reviews were analyzed and paraphrased.Results: smartphone addiction is the major reason for poor academic performance of the students.Conclusion: The smartphones must be assessed for their usability and suitability to be used by the students.The phones maybe of a great help to a student if he sees learning opportunities in it.